EKSPRESI Tumor Necrosis Factor alpha (TNF-α) DAN Transforming growth factors beta (TGF-β) PADA PERIODONTITIS APIKALIS KRONIS AKIBAT INDUKSI Enterococcus faecalis PADA TIKUS WISTAR - Richard Fritzgerald; Cecilia lunardhi; Ruslan Effendy; Tamara Yuanita (Universitas Airlangga, 2017)
Background. Root canal treatment is a main role in decreasing infection from root canal and pulp. The main cause of periapical damage mostly are bacteries. E.faecalis is a bactery that is found as an etiology of endodontic treatment failure. Cell wall of this bacteria is containing Lipoteichoic acid (LTA). LTA can penetrate into the periradicular tissue, act as endotoxin in host and cause periradicular inflammation then lead to bone destruction. LTA stimulates immunology reaction that produce Tumor Necrosis Factor alpha (TNF-α) and Transforming growth factors beta (TGF-ß). TNF-α is a main mediator and also have an important role in inflamation response otherwise TGF-ß is working as a multifunction regulator of cell growth and differentiation during reforming and remodelling. Purpose. The aim of this study is to know about the expression of TNF-α and TGF-ß during the periapical tissue damage due to induction of E.faecalis. Method. This study used laboratory experimental with the post test only control group design. A total of 30 male rats were randomly divided into 3 main groups, Group A (control negative) : normal tooth. Group B (control positive) : every tooth was induced only by sterile BHI-b. Group C (treated group) : every tooth was induced by 10 μl BHI-b E.faecalis ATCC212(106 CFU). The animals were sacrificed 21 days later and prepared for histological examination of tissue damage, then we did the immunohistochemistry followed by calculation on the light microscope. Result. The analysis revealed that the expression of TNF-α at treated group are higher than negative control and positive control but the expression of TGF-ß at treated group are higher than the negative control group but lower than positive control. Conclusion. From this study we know that the expression of TNF-α and TGF-ß are changing during the periapical tissue damage that induced by E.faecalis.